The Principle of Legality in International Criminal Law - Lutfiu, Nuredin; Halimi, Besim (Journal of Posthumanism, 2025)
The Latin formulation "nullum crimen, nulla poena sine lege" is a principle in criminal law. This generally accepted principle of legality means that no one can be punished for a conduct without it being provided by law as a punishable offense. This principle has a guaranteeing function in the protection of the rights and freedoms of citizens and the realization of the rule of law. The dominant worldview is that now in international criminal law, instead of the principle "nullum crimen sine lege", it is enough to respect the principle "nullum crimen sine iure". This is based on the fact that international criminal law will not be directly applied, but must first be included in domestic criminal law. The newest doctrine starts from the fact that we should not insist literally on the law, but on some adequate international legal act (nullum crimen sine actu). In fact, this would imply the need to adopt an international criminal code (despite its name), which in reality cannot be expected to be adopted in the near future. The adoption of the Statute of the International Criminal Court is a step in this direction. In the continuation of this paper, we will examine the main conditions that must be met by future international legislation dedicated to the effective implementation of the principle of legality in international criminal law.